Gerakan Affirmasi Untuk Kesetaraan: Kuota 30%, Peran DPIA dan Representasi Perempuan Aceh di Parlemen - Tri Fitriani Puspitasari (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2018)
This paper discusses the Affirmation Movement conducted by Aceh women in improving their representation in Parliament. Women now have a more open opportunity to engage in policy-making, especially with regard to budgeting and women's empowerment in politics. The purpose of this paper is to identify three things, first, it is necessary to have a strong female character to win female candidates in legislative elections in Aceh. Second, that there is a significant difference between Deliberative democracy initiated by Habermas and the Acehnese women's movement. Third, look at any movements carried out by the DPIA to win female candidates. The method used is the explanatory Qualitative method and using Participatory Action Research (PAR) for data collection method, where researchers are directly involved in several movement agendas.There are numerous social organizations that grew up after the Helsinki negotiations focusing on women's empowerment. The organizations then formed a network called Inong Aceh Inshore Center and held the Great Congress of Aceh Women named DPIA (Duek Pakat Inong Aceh). One of the DPIA's agenda is to win women candidates in legislative and political education elections. The main question of this paper is